Notification and counselling of hepatitis positive blood donors, their immediate emotional response, contact-testing and their follow-up: Study from a tertiary care hospital!. Issue 3 (June 2018) - Tiwari, Aseem K.; Bhardwaj, Gunjan; Dara, Ravi C.; Arora, Dinesh; Aggarwal, Geet; Bhargava, Richa; Madan, Kaushal
Abstract: Introduction: Post-donation counselling informs donors of unusual test results. Timely notification and counselling regarding their Transfusion Transmitted Infection (TTI) status is necessary for early clinical intervention in the donor and reducing risk of transmission. We share our experience with respect to Hepatitis B (HBV) and Hepatitis C (HCV) positive donors who were counselled and followed-up for clinical outcome. Materials and methods: It was prospective 2-year study in TTI positive blood donors. Confirmed positive HBV/ HCV donors were notified to attend the donor-clinic or to visit local hepatologist for further management. At donor clinic, donor's immediate emotional response was observed; donors were offered contact-testing, associated risk factors were noted, counselled, referred to hepatologist, treated and followed-up for clinical outcome. Results: Of 481 donors (0.91%) confirmed positives, 351 were contacted telephonically; 280 promised to attend donor clinic and 71 were referred to their local hepatologist. 145 donors attended the donor clinic, eventually. Most common immediate emotional response noted were 'feeling of fear' (55.2%) and 'disbelief' (35.2%). Most common associated risk factor was history of medical treatment/ injections without knowledge of sterilisation. Five donors availed contact testing and four (spouses in all four cases) came out positive. Of 98 donors contacted post-counselling; 89 went to hepatologist. No medication was advised to seven donors (low viral load), 59 donors completed treatment course and 23 donors were undergoing treatment at time of follow-up. Nine donors opted for alternative treatment or "no treatment". Conclusion: Donor-clinic proved beneficial to substantial number of donors and their families.